Hyatt's interpretation of pulmonary function tests : a practical guide - Scanlon, Paul D. (Paul David); Hyatt, Robert E. (Wolters Kluwer, 2020)
"This book provides a solid basis for administering and interpreting pulmonary function tests and offers valuable guidance for day-to-day clinical work, featuring chapters such as "When to Test and What to Order" and "Approaches to Interpreting Pulmonary Function Tests." Features a new section on the interpretation of complex tests, including the nonspecific pattern, mixed obstruction with restriction, and the complex restrictive pattern. Includes more than 40 illustrative cases for self-testing and reinforcing the principles discussed in the text, as well as clear illustrations that demonstrate dozens of PFT patterns. Contains expert "pearls" regarding performance and interpretation of key tests." -- Provided by publisher.